Association of the von Hippel-Lindau protein with AUF1 and post-transcriptional regulation of Vascular Endothelial Growth Factor A mRNA - Xin, Hong (2011)
The von Hippel-Lindau (VHL) tumor suppressor gene product is the recognition component of an E3 ubiquitin ligase and is inactivated in patients with VHL disease and in most sporadic clear cell renal carcinomas (RCC). pVHL controls oxygen-responsive gene expression at the transcriptional and post-transcriptional levels. The vascular endothelial growth factor A (VEGFA) mRNA contains AU-rich elements (AREs) in the 3' untranslated region, and mRNA stability or decay is determined through ARE-associated RNA binding factors. We show here that levels of the ARE binding factor, AUF1, are regulated by pVHL and by hypoxia. pVHL and AUF1 stably associate with each other in cells and AUF1 is a ubiquitylation target of pVHL. AUF1 and another RNA binding protein, HuR, bind to VEGFA ARE RNA. Ribonucleoprotein (RNP)-immunoprecipitations showed that pVHL associates indirectly with VEGFA mRNA through AUF1 and/or HuR, and this complex is associated with VEGFA mRNA decay under normoxic conditions. Under hypoxic conditions pVHL is downregulated, while AUF1 and HuR binding to VEGF mRNA is maintained, and this complex is associated with stabilized mRNA. These studies suggest that AUF1 and HuR bind to VEGFA ARE RNA under both normoxic and hypoxic conditions, and that a pVHL-RNP complex determines VEGFA mRNA decay. These studies further implicate the ubiquitin-proteasome system in ARE-mediated RNA degradation.